Pengaruh informasi akuntansi terhadap keputusan kredit yang diambil oleh bank dan hubungannya dengan pengembalian pinjaman debitur = Effect Accounting Informastion on Credit Decisions Made byThe Bank and Relationship ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
This research is an empirical study of banks in the province of East Kalimantan. Its aim is to obtain empirical evidence on whether accounting information has any effects on and relationships with credit decisions made by the banks under study and its relationship with loan payment. The research population consisted of credit proposals made by creditors who obtained credit facilities from banks in 1990. Sampling was done through two cluster sampling method. The data were collected directly by means of a list of questions distributed to banks under study. The data were then analysed using multiple regression analysis to test the factors or varibles suspected to affect credit decision and loan payment. These varibles were accounting information and non-accounting information. The findings of the research suggests that accounting information affects credit decisions by bank. Accounting information which had a significant effect on credit decisions were the feasibility and growth of the creditors businesses. The effect of accounting information was small, i.e. 17%, which means that credit decisions can still be explained by other variables not included in the regression model. In other words, the research empirically found that accounting was used in making credit decision, even though its effect was small. However, it did not have any significant relationship with loan payment. Factors which affected loan payment were non-accounting variables, i.e. credit terms and the diversification of the creditors businesses. The fact that accounting information did not affect loan payment might have been due to the invalidity of the information obtained from the creditors financial reports, which did not comply with accounting standards. Consequently, the information used in making credit decisions resulted in inaccurate conclusions. An attempt need to be taken to improve the quality of information provided by the debtors.